Interação familiar-bebê na aquisição interdependente dos repertórios ouvinte-falante - Vilas Boas, Denise de Lima Oliveira (2014)
The study of acquisition and development of verbal behavior should be directed to the analysis of environmental variables interacting with the child during learning process. It is important to begin as a descriptive analysis of the baby´s interaction with the environment, focusing historical variables that influenced and influence his/hers verbal responses. Therefore, the objective of the present research was to describe which contingencies are involved in the development of a baby´s verbal repertoire from birth until 13 months, seeking to identify the teaching procedures used. The reach this goal, videos made by the baby´s family from birth until 18 months old were used. From this initial data collection, the videos were watched and 120 of them, summing up to four hours, 25 minutes and 20 seconds, were used. All videos were transcribed in a timeline in which the baby´s and his/her family´s vocal and motor responses were registered second by second. The family-child interaction responses were analyzed in sequence from arbitrary video sections in order to define contingencies (family-child). Synthesizing the baby´s verbal repertoire development process until 13 months allowed the identification of a listener repertoire before a speaker repertoire began being shaped, with these processes occurring almost together. One contribution of this research is that it conducted a behavioral synthesis, employing what was drawn from other studies in a unique process. The objective and synchronized log of the baby and the family´s vocal and motor responses allowed an analysis of the dependent relations between changes in the family´s and baby´s repertoire, representing a methodological contribution for descriptive studies. Due to the non systematic data collection, although continuous, it cannot be stated that the time periods analyzed as the first ones were actually the first in the baby´s life. Nevertheless, due to the systematic data collection, it can be stated that they occurred in the described order and in periods very close to the first. A lot of other studies of this sort need to be made to generalize the data